SOME ASPECTS OF THE AGGRESSIVE ACTS, COMMITTED BY SCHIZOPHRENIC PATIENTS, TRIGGERED BY SOME PSYCHO-TRAUMATIC FACTORS - Stefan Todorov; Mariana Arnaoudova (Peytchinski Publishing, 2012)
The achievements of the contemporary psychopharmacology enable the out-patient treatment of schizophrenic patients, thus let them living in their usual social environment- family, relatives, neighbors, friends.In this connection, the real conditions of patients' micro-social environment play an important role- either stimulating their compensatory mechanisms, or exercising negative impact on their adaptation and behavior.We examined 30 schizophrenic patients (22 males, 8 females), who have committed aggressive acts, triggered by psycho-traumatic situations with different sensible content, originating from their micro-social environment.Dominant were family conflicts, followed by conflicts with the neighbors. The aggressive acts were directed to concrete persons, from the close neighborhood, involved into the psycho-traumatic situations.Studying and evaluation of the aggressive acts, triggered by psycho-traumatic factors play an important role for their prevention.